Comparison of preoperative and postoperative sexual function in patients with deeply infiltrating endometriosis with and without bowel resection. (August 2019) - Lermann, Johannes; Topal, Nalan; Renner, Stefan P.; Beckmann, Matthias W.; Burghaus, Stefanie; Adler, Werner; Heindl, Felix
Abstract: Objective: To analyze preoperative and postoperative sexual function following surgery for deeply infiltrating endometriosis (DIE) with and without bowel involvement. Study design: Patients with DIE who underwent surgery between 2001 and 2011 with segmental bowel resection (WB) or without segmental bowel resection (WOB) were surveyed using the German version of the Massachusetts General Hospital Sexual Functioning Questionnaire (KFSP). Responses were given on a six-point scale for the items sexual interest, sexual arousal, orgasm, lubrication, and general sexual satisfaction. As there are no cut-off values for the existence of sexual function disorders, a control group with no history of endometriosis was evaluated. Differences between the preoperative and postoperative results, as well as between WB, WOB, and a control group, were compared using the Wilcoxon test, Mann–Whitney U test, and Fisher's exact test. Results: Eighty-nine patients without bowel resection (mean age 34.3 years; mean follow-up 63.2 months), 87 patients with bowel resection (mean age 37.7 years; mean follow-up 69.6 months), and 100 control patients aged 21–58 years (mean age 35.0 years) were evaluated. Preoperatively, both treatment groups had significantly poorer scores in all categories in comparison with the control group. The WOB group improved significantly in all categories postoperatively, with no further significant differences from the control group. No significant postoperative improvement was observed in the WB group, and the group had significantly poorer scores in comparison with the control group. The number of previous operations is associated with significantly poorer postoperative KFSP results. Sterility and age > 40 years are associated with significantly less improvement in the KFSP, although with lower initial values. Conclusions: Patients with DIE with or without bowel involvement have significantly impaired sexual function preoperatively. Complete resection of endometriosis in the WOB group was able to improve sexual function, as the women had sexual scores similar to those in the healthy control group postoperatively. Possible explanations for the lack of postoperative improvement of sexual function after segmental bowel resection include the type of surgery carried out, or injury to the affected nerves resulting from the endometriosis.